Change and continuity in the EU's 'state building-security nexus' in Ukraine. A historical institutional perspective - Lucian Dumitrescu (EURINT)
While the 2014 Annexation of Crimea has been presented by the scholarly literature as leading only to an incremental change in the state-building and foreign policy practices of the EU towards Ukraine, the 2022 invasion of the Russian Federation has been assessed as a critical juncture that has finally turned the EU into a geopolitical actor. The research question that my presentation seeks to answer to is whether the dynamic of the EU's 'state-building security nexus' in Ukraine could be looked at with a different conceptualization of institutional change, one that goes beyond the already traditional dichotomy between incremental change triggered by endogenous factors and the radical change that could be caused by a critical juncture like the 2022 War in Ukraine. By relying on historical institutionalism - an approach that still tries to find its place in an academic field that is clearly dominated by either rational institutionalism or constructivist institutionalism -, I trace two aspects of institutional change, i.e., speed and depth, that the EU's 'state building - security nexus' has undergone since 2014. Specifically, I bring under scrutiny three types of evolutions related to the EU's 'state-building security nexus' in Ukraine: strategic thinking, state building practices, and foreign policy actions. As I am interested in the evolution of the abovementioned aspects in the long run, my presentation also seeks to trace their dynamic after 2022. To this end, I employ process tracing as a research method, while the data that I use come from both primary sources, i.e., official documents of the EU, and secondary sources, that is, scholarly literature.